Probing restarting activity in hard X-ray selected giant radio galaxies. Issue Volume 14:Issue A30(2018) (August 2018) - Bruni, G.; Ursini, F.; Panessa, F.; Bassani, L.; Bazzano, A.; Bird, A. J.; Chiaraluce, E.; Dallacasa, D.; Fiocchi, M.; Giroletti, M.; Hernández-García, L.; Malizia, A.; et al.
Abstract: With their sizes larger than 0.7 Mpc, Giant Radio Galaxies (GRGs) are the largest individual objects in the Universe. To date, the reason why they reach such enormous extensions is still unclear. One of the proposed scenarios suggests that they are the result of multiple episodes of jet activity. Cross-correlating the INTEGRAL+Swift AGN population with radio catalogues (NVSS, FIRST, SUMSS), we found that 22% of the sources are GRG (a factor four higher than those selected from radio catalogues). Remarkably, all of the sources in the sample show signs of restarting radio activity. The X-ray properties are consistent with this scenario, the sources being in a high-accretion, high-luminosity state with respect to the previous activity responsible for the radio lobes.